2013
DOI: 10.1016/j.jaut.2013.06.001
|View full text |Cite
|
Sign up to set email alerts
|

The autoimmune disease-associated SNP rs917997 of IL18RAP controls IFNγ production by PBMC

Abstract: Type 1 Diabetes (T1D) is an autoimmune disorder characterized by aberrant T cell responses. Innate immune activation defects may facilitate a T helper 1 (Th1) phenotype. The cytokine IL-18 synergizes with IL-12 to induce IFNγ production and Th1 differentiation. The IL-18R subunit (IL18RAP) SNP rs917997 has been linked to decreased IL18RAP gene expression. Prior reports link rs917997 allele A with protection from T1D, and conversely with susceptibility to Celiac disease. However, few studies have investigated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…However, at each of the following 6 time points, the Tr14-treated group shows a moderate, but reproducible increase in expression levels. IL18RAP has been shown to regulate interferon-γ production in peripheral blood monocytes (Myhr et al, 2013 ), and so this increase might reflect altered monocytic infiltration.…”
Section: Resultsmentioning
confidence: 99%
“…However, at each of the following 6 time points, the Tr14-treated group shows a moderate, but reproducible increase in expression levels. IL18RAP has been shown to regulate interferon-γ production in peripheral blood monocytes (Myhr et al, 2013 ), and so this increase might reflect altered monocytic infiltration.…”
Section: Resultsmentioning
confidence: 99%
“…The SNP rs917997 A/A in the IL18RAP gene, which is associated with a number of diseases, is a loss‐of‐function allele that impairs the correct activation of macrophages in response to inflammatory stimuli, thus implying a key role for the accessory chain IL‐1R7 in innate defense. In another study, the rs917997 G/G phenotype was associated with increased expression of IL‐1R7 and increased responsiveness of peripheral blood mononuclear cells to IL‐18/IL‐12 in terms to IFN‐γ production …”
Section: Focus On the Il‐1r Familymentioning
confidence: 93%
“…The SNP rs917997 A/A in the IL18RAP gene, which is associated with a number of diseases, is a loss-of-function allele that impairs the correct activation of macrophages in response to inflammatory stimuli,240 thus implying a key role for the accessory chain IL-1R7 in innate defense. In another study, the rs917997 G/G phenotype was associated with increased expression of IL-1R7 and increased responsiveness of peripheral blood mononuclear cells to IL-18/IL-12 in terms to IFNγ production 241. Binding of ligands: Mechanisms, critical amino acid residues, and affinityIt was reported that IL-18 binds to its ligand-binding chain IL-1R5 with a K d of 3-94 nM, and that recruitment of the accessory protein IL-1R7 can significantly increase affinity (K d 0.3-0.4 nM) (see aboveSection 3.2.4.1).…”
mentioning
confidence: 93%
“…29,30 On the other hand, rs917997 polymorphism has been described as a protective factor against T1D while a risk factor for CD in another report. 68 The rs917997, a polymorphism located in the 3′ UTR, has been accompanied by depressed levels of IL18RAP in the serum of individuals with CD. 62,69 Another polymorphism of this gene, rs13015714 was not found to exert a significant influence on the occurrence of CD.…”
Section: Sh2b Adaptor Proteinmentioning
confidence: 99%